Potential of Basil (Ocimum basilicum) leaf extract in Tris-egg yolk extender on sperm motility and plasma membrane integrity of Sapudi ram at room temperature - Pratama Putra Banusiandana; Suherni Susilowati; Sri Mulyati; Tri Wahyu Suprayogi; Emy Koestanti Sabdoningrum; Nove Hidajati (Universitas Airlangga, 2025)
This study aimed to determine the effect of basil (Ocimum basilicum) leaf extract in a Tris-egg yolk extender on the motility, and plasma membrane integrity of Sapudi ram spermatozoa at room temperature. Fresh semen samples were collected from Sapudi ram using an artificial vagina. A completely randomized design was used, consisting of four treatment groups with five replicates each. Data were analyzed using SPPS with factorial analysis of variance (ANOVA) and Duncan’s test. The control group (T0) received Tris-egg yolk extender without basil leaf extract. Treatment groups T1, T2, and T3 received 1%, 2%, and 3% basil leaf extract, respectively, in the extender. Results showed that sperm motility and plasma membrane integrity (Table 4) tended to decrease with increased storage time. Among the treatment groups, the addition of 1% basil leaf extract in the Tris-egg yolk extender (T1) resulted in significantly higher (p <0.05) both sperm motility and plasma membrane integrity compared to the control (T0). However, higher concentrations of basil leaf extract (T2 and T3) did not result in significant differences (p >0.05) in sperm motility after three hours of storage compared to the 1% treatment (T1). In conclusion, the addition of 1% basil leaf extract to a Tris-egg yolk extender was effective in maintaining sperm motility and plasma membrane integrity of Sapudi ram spermatozoa stored at room temperature for up to three hours.